Chinese belt and Road initiative:its investment protection and dispute resolution in Pakistan - Akhtar, Naeem (Riga Graduate School of Law, 2020)
Chinese Belt and Road initiative is a global investment strategy of regional connectivity. It has gained enormous importance due to its mega investment projects in many countries through Asia, Europe, and Africa. This research is based on a study of the existing legal framework of investment protection and dispute settlement of BRI projects in Pakistan. The main aim of this thesis is to analyze the effect of domestic laws of China and Pakistan, respectively, on the outcome of investment protection and dispute resolution of BRI projects in Pakistan. The role of domestic laws and efficient dispute resolution system of the host state cannot be ignored in international investment law. This research identified that lack of ADRs system with weak domestic investment and arbitration laws in Pakistan are significant constrains to ensure optimal investment protection & disputes settlement of BRI projects. This thesis will advance the debate of establishing a more sustainable investment protection regime and unified dispute resolution mechanism for future BRI disputes.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Dispute settlement; Investment law; Pakistan